Analisis Kesalahan dalam Menyelesaikan Soal Bentuk Aljabar pada Siswa Kelas VII SMPN 2 Lingsar Tahun Ajaran 2021/2022 - Ridha Surgana; Nani Kurniati; Eka Kurniawan; Sudi Prayitno (Griya Journal of Mathematics Education and Application, 2022)
This research aims to find out the mistakes made by students and the factors that cause mistakes made by students in solving algebraic form problems in terms of Polya steps. This type of research is descriptive and qualitative. The sample used was 28 students with the sampling technique used being proportionate stratified random sampling. Data collection techniques are carried out by tests and interviews. Based on the analysis of student test results, error were obtained by students in each question item, namely, errors in understanding the problem, errors in drawing up plans, errors in implementing plan, and errors in re-examining. The results showed that the percentage of mistakes made by students in the whole question was 44% errors in understanding the problem with sufficient categories, 36% errors in drafting plans with low categories, errors in implementing plan by 33% with low categories, and errors in re-examining by 61% with high category. The cause of students' mistakes in solving algebraic form questions is that students are not careful in reading the questions and in writing down their work, do not understand the questions or prerequisite materials, both the nature, formulas, or procedures for working on the questions, the desire to answer briefly to things that are known and asked. As well as students are not used to re-examining.